Efficacy of radiotherapy in combination with first-line immunotherapy and chemotherapy for advanced lung squamous cell carcinoma: a propensity score analysis - Qin, Jian; Yi, Shouhui; Zhou, Hanjing; Zeng, Chuan; Zou, Minghua; Zeng, Xuan; Yang, Zhenzhou; Huang, Yusheng (Frontiers in Immunology, 2023)
Aim To compare the efficacy and safety of radiotherapy in combination with immunotherapy after achieving disease control from the first-line combination therapy of platinum-based chemotherapy and immunotherapy for advanced lung squamous cell carcinoma (LUSC). Methods This study retrospectively evaluated the patients with advanced LUSC treated with the combination of radiotherapy with immunotherapy and chemotherapy (ICRT group, n = 52) or immunotherapy and chemotherapy (ICT group, n = 63) as the first-line treatment from April 2018 to April 2022. Using propensity score matching (PSM), 50 pairs were created, while the confounders and bias were controlled. The objective response rate (ORR), duration of overall response (DOR), progression-free survival (PFS), overall survival (OS), and adverse events were analyzed in the two groups. The PFS and OS were re-analyzed separately for patients treated with thoracic radiotherapy. Results After PSM, the median PFS (12.23 vs. 7.43 months; P <0.001) and median OS (19.7 vs. 12.9 months; P <0.001) were significantly longer in the ICRT group than those in the ICT group. Both the PFS and OS rates were also significantly higher in the ICRT group than those in the ICT group, except for the OS rates in the 6th and 12th months. The mDOR of the ICRT group patients (17.10 vs. 8.27 months; P <0.001) was significantly higher than that of the ICT group patients. The median PFS, median OS, and local control rate were significantly longer in the thoracic radiotherapy group than in the control group. Radiation pneumonia was the most common adverse effect after radiotherapy; however, no treatment-related deaths occurred. The Cox regression analysis showed that ECOG scores 0-1, presence of necrosis in the tumor, radiotherapy, and optimal efficacy better than the stable disease (SD) were independent factors, affecting the PFS, while the patients with recurrent post-operative, pre-treatment NLR, radiotherapy, and optimal efficacy better than SD were the independent factors, affecting the OS. Conclusions The combination of radiotherapy with systematic immunotherapy and chemotherapy for the advanced LUSC was effective with tolerable adverse effects.